The Impact of Globalization and Technology Transfer on Manufacturing Employment and Skills in Ethiopia - Getinet Astatike Haile; Ilina Srour; Marco Vivarelli (Institute for the Study of Labor (IZA), 2013)
There is a dearth of research on the impact of technological change on employment in the context of least developed countries (LDCs) embarking on globalization, which enhances the prospect of direct technological imports or embodied technological transfer. Using a sample of 1,940 enterprises from Ethiopia over the period 1996-2004 and deploying System Generalized Method of Moments (GMM-SYS), this paper attempts to establish the nature of manufacturing employment in Ethiopia and the role played by trade and FDI in determining employment. The empirical results obtained lend support to globalization having a labour-augmenting effect, increasing total manufacturing employment. The two-equation dynamic framework implemented to analyse enterprise-level employment trends by skill level provides some evidence of skill-bias specific to enterprises with higher share of foreign ownership and those that that are located in the vicinity of the capital city. Exporters are not found to benefit from learning by exporting.
Keywords: O33; F16; L60; O55; C33; 330; technological change; trade; FDI; globalization; skills; employment; Ethiopia